The Influence of Confucian Ethics and Collectivism on Whistleblowing Intentions: A Study of South Korean Public Employees - Park, Heungsik (Journal of business ethics, 2005)
The current study presents the findings of an empirical inquiry into the effects of Confucian ethics and collectivism, on individual whistleblowing intentions. Confucian Ethics and Individualism–Collectivism were measured in a questionnaire completed by 343 public officials in South Korea. This study found that Confucian ethics had significant but mixed effects on whistleblowing intentions. The affection between father and son had a negative effect on internal and external whistleblowing intentions, while the distinction between the roles of husband and wife had a positive effect on those intentions. The effects of collectivism were also different depending on the specific types of collectivism. Horizontal collectivism had a positive effect on both types of whistleblowing intentions, whereas vertical collectivism did not show any significant effects on whistleblowing intentions. These results indicate that cultural traits such as Confucian ethics and collectivism may affect an individual’s whistleblowing intentions in degree and direction, making blanket predictions about cultural effects on whistleblowing difficult.